2019
DOI: 10.3389/fimmu.2019.01299
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros Zinc Finger Transcription Factors: Regulators of Cytokine Signaling Pathways and CD4+ T Helper Cell Differentiation

Abstract: CD4 + T helper cells are capable of differentiating into a number of effector subsets that perform diverse functions during adaptive immune responses. The differentiation of each of these subsets is governed, in large part, by environmental cytokine signals and the subsequent activation of downstream, cell-intrinsic transcription factor networks. Ikaros zinc finger (IkZF) transcription factors are known regulators of immune cell development, including that of CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 91 publications
(136 reference statements)
2
54
0
Order By: Relevance
“…Indeed, this antagonism may largely explain the tumor suppressor function of Ikaros in BCP-ALL, where IKZF1 loss-of-function mutations are most prevalent in subtypes exhibiting activated JAK/STAT5 signaling. These results have implications beyond the B cell lineage, as STAT5 and Ikaros family proteins are also important for T cell activation and polarization downstream of IL-2 and IL-7 signaling [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this antagonism may largely explain the tumor suppressor function of Ikaros in BCP-ALL, where IKZF1 loss-of-function mutations are most prevalent in subtypes exhibiting activated JAK/STAT5 signaling. These results have implications beyond the B cell lineage, as STAT5 and Ikaros family proteins are also important for T cell activation and polarization downstream of IL-2 and IL-7 signaling [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The members of the Ikaros family of zinc finger (Ikzf) transcription factors have a crucial role not only in immune cell development and homeostasis, but also pathological conditions in human [21, 44]. It has been reported that deregulation of IKAROS, the founding member of the family encoded by the Ikzf1 gene, results in leukemia in both mice and human [45], whereas downregulation of EOS, encoded by the Ikzf4 gene, induces a regulated conversion of Tregs into T helper-like cells that are capable of secreting proinflammatory cytokines in response to specific inflammatory signals [20].…”
Section: Discussionmentioning
confidence: 99%
“…Th2 effector T cells are involved in the defense against parasitic infections, allergic reactions and the resolution of chronic inflammation (60). Unlike the previously discussed Th1 effector cells, the mechanisms driving Th2 differentiation are still not fully understood.…”
Section: Th2 Cellsmentioning
confidence: 99%
“…All of these factors result in a skewing from Th2 to Th1 (69). Despite this growing pool of knowledge on the regulatory mechanisms ascribed to Ikaros, very little is known about the regulation of Ikaros itself in T cells (60,70). However, a recent study of Ikaros regulation in B cells may provide insight into a conserved IRF5-dependent Ikaros regulatory mechanism in T cells (45).…”
Section: Th2 Cellsmentioning
confidence: 99%